Effects of garlic on the induction of ventricular fibrillation - Sungnoon R. (2014)
Previous studies have shown that oral and intravenous administrations of garlic provide a significant antiarrhythmic effect and improve defibrillation efficacy. We tested the hypothesis that garlic could decrease the inducibility of ventricular arrhythmia.